Transnational Patients: Practical and Ethical Implications for Medical Practices and Health Promotions Policy. Issue 2 (23rd May 2018) - Zeldes, Nina; Dilger, Hansjörg; FitzGerald, Kevin; Kohls, Niko; Moore, Eileen; Nöfer, Eberhard; Giordano, James
Abstract : Health care is becoming increasingly transnational and a shift to more promotive and preventative approaches forms an integral part of addressing challenges to global health and health disparities. Community and public engagement programs are particularly well suited to successfully developing care that is resonant and meaningful in transnational contexts. Yet many existing programs do not take into account the diverse perspectives of the heterogeneous group of transnational patients, and guidelines that address their specific needs are still scarce. At the same time, little has been done to build a framework to share successful local programs with a broader community. We thus propose a global database of best practices and guidelines for transnational health‐care promotions to improve health care and well‐being across diverse communities, consisting of a three‐step assessment in order to successfully design locally adapted programs that are accepted by target populations and successfully engage transnational patients and their health‐care providers.